1997
DOI: 10.1192/bjp.171.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Disability, outcome and case-mix in acute psychiatric in-patient units

Abstract: Routine outcome assessment using reliable and valid instruments is practical, and could lead to improvements in the quality of care for psychiatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
52
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 2 publications
11
52
0
2
Order By: Relevance
“…LOS was directly correlated with score on the BPRS positive symptoms subscale; very low scores (1-10) were associated with decreases in LOS while very high scores (31)(32)(33)(34)(35)(36)(37)(38)(39)(40) were associated with a greater than 82% increase. This suggests that the BPRS positive symptom subscale might be used to identify patients with potentially longer LOS.…”
Section: Clinical Factorsmentioning
confidence: 97%
See 2 more Smart Citations
“…LOS was directly correlated with score on the BPRS positive symptoms subscale; very low scores (1-10) were associated with decreases in LOS while very high scores (31)(32)(33)(34)(35)(36)(37)(38)(39)(40) were associated with a greater than 82% increase. This suggests that the BPRS positive symptom subscale might be used to identify patients with potentially longer LOS.…”
Section: Clinical Factorsmentioning
confidence: 97%
“…Prior research has found increased LOS among geriatric psychiatric patients to be associated with falling while hospitalized (16)(17)(18)(19)(20)(21)40), inability to return to prior living arrangement (1,20,33), ECT (16,17), and greater severity of psychiatric illness (23,36,37,41,42). On the other hand, cognitive impairment (21,22) has not been found to influence LOS.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…An exception is the study that examined long-stay patients in a psychiatric hospital and showed that only 26% of the patients were able to answer the World Health Organization Quality of Life (WHOQOL), a questionnaire about QOL [13]. Another exception is the study of an acute inpatient setting in which the use of the SF-36 for outcome assessment proved not feasible [12]. Unlike the present study, these studies only address a feasibility issue surrounding the use of self-report measures of QOL.…”
Section: Discussionmentioning
confidence: 93%
“…A number of studies have begun to demonstrate that older adults with severe cognitive impairment are not capable of completing a subjective QOL assessment reliably and validly [7][8][9][10][11], but only a few studies validate QOL questionnaires in psychiatric patients with a broad spectrum of disabilities [12,13]. The aim of this study, therefore, was to clarify the measurement limit of a QOL questionnaire by examining data quality, reliability, and validity in psychiatric patients.…”
Section: Introductionmentioning
confidence: 98%